2016
DOI: 10.1007/s11418-016-1045-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole alkaloids from Murraya koenigii trigger apoptosis and autophagic flux inhibition in human oral squamous cell carcinoma cells

Abstract: Carbazole alkaloids, a major constituent of Murraya koenigii (L.) Sprengel (Rutaceae), exhibit biological effects such as anticancer activity via the induction of apoptosis, and they represent candidate chemotherapeutic agents. Oral squamous cell carcinoma (OSCC) is the most prevalent cancer of the oral cavity and a growing and serious health problem worldwide. In this study, we investigated the anticancer properties and mechanisms of action of two carbazole alkaloids derived from M. koenigii leaves, mahanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…4A). Mahanine was shown to induce cell death in human cancer cells through inhibiting the autophagic degradation activity, a mechanism different from cisplatin (Utaipan et al 2017). Treatment for 24 h with mahanine at 25 µM significantly decreased the viability of HepG2 hepatocellular carcinoma cells and HuCCT1 and KKU-100 cholangiocarcinoma cells (Fig.…”
Section: Induction Of Mitf Expression By Mahanine In Hepatic Cancer Cmentioning
confidence: 91%
See 2 more Smart Citations
“…4A). Mahanine was shown to induce cell death in human cancer cells through inhibiting the autophagic degradation activity, a mechanism different from cisplatin (Utaipan et al 2017). Treatment for 24 h with mahanine at 25 µM significantly decreased the viability of HepG2 hepatocellular carcinoma cells and HuCCT1 and KKU-100 cholangiocarcinoma cells (Fig.…”
Section: Induction Of Mitf Expression By Mahanine In Hepatic Cancer Cmentioning
confidence: 91%
“…Moreover, mahanine was reported to inhibit the autophagic degradation activity in human oral squamous cell carcinoma cells (Utaipan et al 2017). Here we have shown that mahanine exerted the potent cell toxicity in the hepatic cancer cell lines, including HuCCT1 cells that were resistant to cisplatin (Samatiwat et al 2016); namely, mahanine may kill hepatic cancer cells through the mechanism different from cisplatin.…”
Section: Implication Of the Mahanine-mediated Induction Of Mitf Exprementioning
confidence: 99%
See 1 more Smart Citation
“…Dexter (DLD-1) colon cancer cells; interestingly, this inhibition of the Akt/mTOR pathway could possibly activate the intrinsic apoptotic program [86]. Mahanine and isomahanine derived from M. koenigii leaves exert anticancer effects on oral squamous cell carcinoma cells via the induction of microtubule-associated protein 1 light chain 3, type II (LC3B-II), and cleaved caspase-3, suggesting the inhibition of autophagic flux [96]. In human leukemic cells, Mahanine was reported to induce apoptosis by interrupting signal transfer between Apo-1/Fas signaling and the Bid protein and via mitochondrial pathways in humans [59].…”
Section: Apoptosismentioning
confidence: 99%
“…It was also observed that 71 and 72 might lead to the generation of ROS, causing mitochondrial dysfunction and triggering apoptosis. Microscopic analysis showed an increased formation of autophagic vacuoles and WB showed increased levels of LC3‐II and p62, suggesting that the two compounds were autophagy inducers able to stop the autophagic flux resulting in autophagic cell death . In another paper by Irimie et al, the activity of epigallocatechin‐3‐gallate ( 73 ), one of the most important bioactive compounds of green tea, was evaluated against OSCC.…”
Section: Autophagy Modulators In Oscc and Esccmentioning
confidence: 99%